The influence of oxygen delivery and oxygen utilization on the determinants of exercise tolerance - Broxterman, Ryan M. (Kansas State University, 2015)
The physiological mechanisms determining the tolerable duration of exercise dictate human physical accomplishments across all spectrums of life. Despite extensive study, these specific mechanisms, and their dependence on oxygen delivery and oxygen utilization, remain, a certain extent, undefined. The purpose of this dissertation was to test the overarching hypothesis that muscle contraction characteristics (i.e., intensity of contraction, muscle contraction-relaxation duty cycle, etc.) alter oxygen delivery and oxygen utilization, which directly influence the power-duration relationship and fatigue development, and therefore, exercise tolerance. To accomplish this, specific interventions of altered muscle contraction-relaxation duty cycle and blood flow occlusion were utilized. In the first investigation (Chapter 2), we utilized low and high muscle contraction-relaxation duty cycles to alter blood flow to the active skeletal muscle, demonstrating that critical power (CP) was reduced with the high muscle contraction-relaxation duty cycle due to a reduction in blood flow, while the curvature constant (W’) was not altered. The second investigation (Chapter 3) utilized blood flow occlusion to show that CP was reduced and W’ increased for blood flow occlusion exercise conditions compared to control blood flow exercise conditions. The final investigation (Chapter 4) utilized periods of blood flow occlusion during and post-exercise to reveal greater magnitudes of peripheral and central fatigue development during blood flow occlusion exercise compared to control blood flow exercise. Moreover, this investigation demonstrated that W’ was significantly related to the magnitude of fatigue development. Collectively, alterations in oxygen delivery and oxygen utilization via muscle contraction characteristics and blood flow occlusion directly influence CP and the magnitude of fatigue development. However, W’ does not appear to be influenced by manipulations in oxygen delivery and oxygen utilization, per se. Rather, W’ may be determined by the magnitude of fatigue accrued during exercise, which is dependent upon oxygen delivery and oxygen utilization. The novel findings of the investigations presented in this dissertation highlight important physiological mechanisms that determine exercise tolerance and demonstrate the need for interventions that improve oxygen delivery and oxygen utilization in specific populations, such as those with chronic heart failure or chronic obstructive pulmonary disease, to improve exercise tolerance.
Keywords: Critical power; Fatigue; Exercise tolerance; Oxygen delivery; Oxygen utilization; Kinesiology (0575); Physiology (0719)